номер 162 гдз 8 класс алгебра Муравин Муравин

1)\begin{equation}a^{-1}+b^{-1} \end{equation} \begin{equation}\frac{1}{a}+\frac{1}{b}=\frac{b+a}{ab} \end{equation}
2)\begin{equation}c^{-2}-y^{-2} \end{equation} \begin{equation}\frac{1}{c^{2}}-\frac{1}{y^{2}}=\frac{y^{2}-c^{2}}{c^{2}y^{2}} \end{equation}
3)\begin{equation}x+y^{-1} \end{equation} \begin{equation}x+\frac{1}{y}=\frac{xy+1}{y} \end{equation}
4)\begin{equation}n^{-1}-m^{2} \end{equation} \begin{equation}\frac{1}{n}-m^{2}=\frac{1-m^{2}n}{n} \end{equation}
5)\begin{equation}\left ( x-y \right )^{-2}=\frac{1}{x-y^{2}} \end{equation}
6)\begin{equation}\left ( n+p \right )^{-3} \end{equation} \begin{equation}\frac{1}{\left ( n+p \right )^{3}} \end{equation}
7)\begin{equation}az^{-3}+a^{-3}z \end{equation} \begin{equation}\frac{a}{z^{3}}+\frac{z}{a^{3}}=\frac{a^{4}+z^{4}}{z^{3}a^{3}} \end{equation}
8)\begin{equation}2c^{-2}+ac^{-1}d^{-2} \end{equation} \begin{equation}\frac{2}{c^{2}}+\frac{a}{cd^{2}}=\frac{2d^{2}+ac}{c^{2}d^{2}} \end{equation}
9)\begin{equation}2x^{-1}+xy^{-2} \end{equation} \begin{equation}\frac{2}{x}+\frac{x}{y^{2}}=\frac{2y^{2}+x^{2}}{xy^{2}} \end{equation}
10)\begin{equation}-5an^{-3}-3an^{-2}+an^{2} \end{equation} \begin{equation}-\frac{5a}{n^{3}}-\frac{3a}{n^{2}}+an^{2}= \end{equation} \begin{equation}=\frac{-5a-3an+an^{5}}{n^{3}} \end{equation}
11)\begin{equation}(x^{-1}-y^{-1})(x-y)^{-2} \end{equation} \begin{equation}\left ( \frac{1}{x}-\frac{1}{y} \right )\cdot \frac{1}{(x-y)^{-2}} \end{equation}
1)\begin{equation}\frac{1}{x}-\frac{1}{y}=\frac{y-x}{xy} \end{equation}
2)\begin{equation}\frac{1}{(x-y)^{2}}=\frac{1}{(y-x)^{2}} \end{equation}
3)\begin{equation}\frac{y-x}{xy}\cdot \frac{1}{(y-x)^{2}}=\frac{1}{xy\left ( y-x \right )} \end{equation}
12)\begin{equation}(x+1)^{-1}+(1-x)^{-1} \end{equation} \begin{equation}\frac{1}{x+1}+\frac{1}{1-x}=\frac{1-x+x+1}{1-x^{2}}=\frac{2}{1-x^{2}} \end{equation}
Play
Play
previous arrow
next arrow
Slider